Economic valuation of non-timber forest products from the tropical dry forest: Ethnic-Pijao, Natagaima-Tolima, Colombia - Pastrana-Aguirre, Gloria Estefanía (2025)
Introduction. Non-timber forest products from the tropical dry forest (TSF) offer multiple benefits and are considered an alternative for the sustainable use of forests and the socioeconomic development of local communities. Nevertheless, little is known about its economic value, limiting the visibility and exploitation of its potential and functionality. Objective. To assess the economic benefits of non-timber forest products from BST for the Pijao indigenous population of Natagaima-Tolima, Colombia. Materials and methods. This study was carried out in the municipality of Natagaima-Tolima, Colombia, during the first half of 2023. Data was collection through semi-structured interviews with 95 indigenous people from the rural sector, integrating social, ethnobotanical and economic variables. For the economic evaluation, the costs required for the acquisition of the product (CRAP), gross profit (BBr) and net profit (Bn) were established, supported by direct, indirect and contingency market valuation methods. Results. 570 reports were registered, 66 species of the tropical dry forest (TSF) were identified, which offer 122 NTFPs, distributed in eight categories of use (food, medicinal, forage, oil, construction, domestic, artisanal and magical-religious). In turn, these offer a total Bn of $ 8,591 /year, with a CRAP of 1.4 and a Bn per person of $ 1.34 /year. The categories of medicinal use, food and forage provide the greatest economic benefits considering that they contribute 79,5 % ($ 6.830,9 /year) of the total net income. Conclusions. NTFPs from tropical dry forests provide important socio-economic benefits to the livel